IMPLEMENTASI KELAS KARAKTER MELALUI THE7AWARENESS DALAM MENINGKATKAN PRESTASI SISWA (STUDI KASUS DI SMP LAB SCHOOL FIP UMJ) - Wasliman, Lim; Sauri, Supyan; Umronih, Dewi; Sulastriningsih , Kursih (Pimpinan Cabang Muhammadiyah Kramat Jati, 2023)
This research is motivated by the decline in the character of the nation's generation which is shown by the decline in the generation's morality in terms of attitudes, language and behavior which influence ethics, so that it requires character strengthening for students, one of which is through Character Classes in schools as learning that supports the improvement of attitudes that originate from awareness. self. This research is descriptive research with a qualitative approach. So the data collection techniques used are observation which aims to observe students' actions in behavior, interviews which aim to obtain information on the actualization of character education at school, and documentation aims to carry out an analysis of the school's readiness to implement character education from an administrative aspect. The results of research conducted show that LabSchool FIP UMJ Middle School is a non-academic education, character classes are considered very important for the mental and spiritual development of students in the current VUCA era, character classes through 7 heart and soul awareness as a form of self-development in improving student achievement at school, research This is important because it proves whether character supports achievement at school. The implementation of character classes can foster positive habits in increasing students' awareness of achieving achievement.